1997
DOI: 10.1159/000262423
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Cariostatic Effect of Resin Modified Glass lonomer Cement and Amalgam on Dentine

Abstract: Fluoride-releasing materials have been reported to be bactericidal in vitro. This may be of benefit to modern dentistry, which is directed to the preservation of tooth tissue during restorative treatment. Little is known about in vivo effects. The aim is to investigate the influence of a resin-modified glass ionomer cement (RM-GIC) on carious dentine that remains under restorations, compared to amalgam. Using a split mouth design, 40 molar pairs in 40 patients (mean age 14.9 years) were selected, based on clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 11 publications
2
35
1
2
Order By: Relevance
“…This finding reinforces the idea that some students continue to follow the basic principle that has regulated operative dentistry for centuries: namely, the removal of all tissue affected by a carious lesion, without considering its extent or depth [26][27][28]. Complete removal of carious dentine is not considered a prerequisite for halting lesion progression [29].…”
Section: Discussionsupporting
confidence: 73%
“…This finding reinforces the idea that some students continue to follow the basic principle that has regulated operative dentistry for centuries: namely, the removal of all tissue affected by a carious lesion, without considering its extent or depth [26][27][28]. Complete removal of carious dentine is not considered a prerequisite for halting lesion progression [29].…”
Section: Discussionsupporting
confidence: 73%
“…Many laboratory studies using, for example bacterial and demineralization-remineralization models, have suggested that GIC will prevent secondary caries. [36][37][38][39][40][41][42] Clinical studies have shown an effect of GIC on salivary fluoride levels, 43 acidogenic bacteria 44 and on demineralized dentine restored with GIC and worn in removable appliances. 45 There is anecdotal clinical evidence that secondary caries in association with GIC is at a very low level.…”
Section: Fluoride Releasementioning
confidence: 99%
“…Some in vivo studies have shown less cariogenic plaque adjacent to GIC restorations 19 and other studies have demonstrated that enamel lesions can be easier remineralized as a result of fluoride release 20 and consequently diminish the risk for recurrent caries at cavity enamel margins 21 . Kreulen et al 22 affirmed that if enamel as well as dentine could benefit from material constituents of glass-ionomer cement, the use of GIC could be a first step towards a new caries therapy. The caries preventive effect of GIC is most likely related to its fluoride release, otherwise it has been shown that an initially high fluoride release decreases after 2-3 months 20 .…”
Section: Discussionmentioning
confidence: 99%